1992
DOI: 10.1038/sj.bdj.4807824
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the TEAMWORK programme

Abstract: The TEAMWORK training programme for DSAs is being used extensively, by experienced staff updating their skills even more than by new recruits. Practitioners are actively involved in the programme and are supporting its use, but there is little awareness of local courses to back up the training being provided. However, specific needs have been identified and could be built upon. Overall, the programme is rated very highly by both training supervisors and trainees, and most practices would use it again.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Other types of CPD activity were reported for England, Latvia and New Zealand. These were: Clinical Audit and Peer Review (8) and Teamwork (9), Keeping in Touch Schemes (for dentists taking career breaks), CPD television programmes and Internet chat rooms.…”
Section: Resultsmentioning
confidence: 99%
“…Other types of CPD activity were reported for England, Latvia and New Zealand. These were: Clinical Audit and Peer Review (8) and Teamwork (9), Keeping in Touch Schemes (for dentists taking career breaks), CPD television programmes and Internet chat rooms.…”
Section: Resultsmentioning
confidence: 99%
“…Four of the most commonly cited reasons for non-attendance, such as distance from postgraduate centres and domestic commitments, suggested that these problems could be overcome by the provision of distance learning materials and programmes. To address the problems a range of videos, 2 manuals 3,4 and computer-aided learning programmes 5 have been developed at public expense 6 and distributed free of charge to dentists working in Primary Dental Care within the NHS. A more recent study 7 indicates that in one English region during the 1990s there has been an improvement in Participating dentists' assessment of the pilot regional online videoconferencing in dentistry (PROVIDENT) project K A Eaton, 1 C A Francis, 2 E W Odell, 3 P A Reynolds 4…”
Section: Education Videoconferencingmentioning
confidence: 99%